A Bibliometric Analysis of Forgiveness in Psychology Literature - Puti Febrina Niko; Yohan Kurniawan; Fairuz A’dilah Binti Rusdi (International Journal of Health and Social Behavior, 2025)
Forgiveness is a challenging process that requires effort and mental streangth as it inovoles complex emotions influenced by external factors. Some group may act harmfully due to unresolved past grievances. While many religious teach selflessness and geniune forgiveness, people often forgive without real intent, wich can lead to continude unhappiness. Studies show that forgiveness can enhance mental helath by reducing feelings like anger and anxiety. Islamic teachings higlight forgiveness’s role in personal and social well-being, lingking it to rewards from Allah and happiness. The study uses the Scopus and PubMed database to analyze research on forgiveness in psychology from 2020to 2025. A total of 2,136 articles on this topic were found. The research offers insights for policymakers and emphasizes the importance of international partnerships for further studies in this area. It also aims to assess research quality, guiding future policies and funding. Overall, this bibliometric analysis effectively identifies research gaps in the field.